Hubungan Pengetahuan Perawat Dengan Pelaksanaan Identifikasi Pasien di Instalasi Gawat Darurat Rumah Sakit X Hubungan Pengetahuan Perawat Dengan Pelaksanaan Identifikasi Pasien di Instalasi Gawat Darurat Rumah Sakit X - Beata Rivani; Sugiyono; Sugiyanti (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction: Patient identification is a process for give a sign or identifier that includes the medical record number and patient identification. The purpose of this research was to determine The Relationship of nurse”s knowledge and implementation of patient identification in hospital emergency installation X. This research method an observational analytic study with cross sectional approach. The number of samples in this study were 40 nurses,this study used a total sampling technique. Results: Most of the respondents had a good level of knowledge 24 respondents (60%), most of the respondents carried out the identification of patients who were still lacking 21 respondents (52.5%) and showed a significant relationship between the knowledge of nurses and the implementation of patient identification in the emergency department of Rs. .X p = 0.001 (p<a = 0.05). The conclusion from this research is the nurses knowledge in the implementation of patient identification in pretty good category. The results of this study can be input in order to more improve their knowledge through seminars and training about patient identification as well as apply the nurses knowledge in the implementation of patient identification.